The importance of cooperation and unity in Islam: the case of Covid-19 - Bendebka, Ramzi (The IIUM COVID-19 Psychological Support Team, 2020)
ometimes, according to His wisdom, Allah will put His servants through trial and test with different types of plagues and diseases at different times and in different places. Currently, COVID-19 is a global threat to human health and human existence with more than two million infections around the world. Governments and societies are trying hard to find methods and practices to effectively engage communities in the attempts to control the virus. This article highlights the role of cooperation and unity from an Islamic perspective as a mechanism to control and minimize the risks of COVID-19.